Finite element analysis on the defected reinforced concrete column [electronic resource] - 448793 Chong, Kean Yee (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2007